1983
DOI: 10.1152/jappl.1983.54.5.1340
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of arterial blood gases at the transition from exercise to rest

Abstract: Arterial blood gas samples obtained 5-20 s after stair-climbing exercise were compared with samples taken during the last 30 s of exercise in 137 subjects. Arterial partial pressure of CO2 (PaCO2) did not change significantly, and in 110 subjects the two samples were within the analytical variation (+/- 2 Torr), supporting the cardiodynamic hypothesis of respiratory regulation. Exceptions to this response were 10 subjects who hyperventilated (PaCO2 less than 34) during exercise and 15 with severe obstruction [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…VD/Vt values in the No Disease group were high in comparison with previous reports [39]. Although the PaCO 2 kinetics immediately following maximal incremental exercise are not known, in a previous study PaCO 2 increased in 25 of 137 subjects following stair climbing exercise [40]. Thus, we suspect that slight asynchrony between the moment mean expired CO 2 was determined (i.e.…”
Section: Discussionmentioning
confidence: 43%
“…VD/Vt values in the No Disease group were high in comparison with previous reports [39]. Although the PaCO 2 kinetics immediately following maximal incremental exercise are not known, in a previous study PaCO 2 increased in 25 of 137 subjects following stair climbing exercise [40]. Thus, we suspect that slight asynchrony between the moment mean expired CO 2 was determined (i.e.…”
Section: Discussionmentioning
confidence: 43%
“…We already know that partial pressure of mixed venous CO 2 (PvCO 2 ) is proportional to the VCO 2 [ 10 ]. The apparent question on the implementation of PvCO 2 instead of the veno-arterial CO 2 difference (PvCO 2 -PaCO 2 ) as an indicator of CO 2 production and exhalation (taking the place of VCO 2 in the ratio) is answered by previous data suggesting that the partial pressure of arterial CO 2 (PaCO 2 ) remains stable during exercise [ 11 ] in contrast with PvCO 2 and VCO 2 that steadily increase during exercise, to a total degree of two times and 16 times, respectively, from rest to peak exercise [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…So the suggested modified index (Mod-RER) that we propose could be: Studies regarding blood partial pressures of O 2 and CO 2 during exercise showed that indeed PvCO 2 is steadily increased, both before and after the anaerobic threshold, following the increase in CO 2 production and expulsion [10]. PaO 2 is slightly increased immediately at the beginning of exercise [11] and as the effort escalates towards the maximum, the PaO 2 values return close to the rest levels [14]. And finally, PvO 2 values do decrease during exercise [15,16] stabilizing at the lowest levels before the advent of anaerobic metabolism without further reduction [17].…”
Section: Developing a Novel Prediction Indexmentioning
confidence: 99%